Preparation and characterization edible film packaging from carrageenan - . Saiful; Siti Saleha; . Salman (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2013)
Preparation of edible film from carrageenan has been studied in this research.  The edible films were made by phase inversion method with various carrageenan concentrations of 1 %, 1.25 %, 1.5 %, and 1.75 % (b/v) and palm oil as plasticizer with variation concentration of 10%, 20% and 30% (v/v). The edible films were characterized for thickness, tensile strength, elongation, oxygen permeability, water absorption capacity, and solubility. The edible film has been applied for slice apple packaging. The optimize edible films structure were obtained with the carrageenan and palm oil compositions of 1.25% and 10% respectively. The characteristics of the edible films have thickness of 0.23 mm, tensile strength of 102.50 kgf/mm2, elongation of 7.04%, oxygen permeability of 7.646 x 10-19 cm3.cm/cm2.s.cmHg. The color brightness test showed significantly different colors at the confidence level of 99.9% and the edible film can prevent 30.7% of weight losses. Edible film can maintain  vitamin C of  99,853%.